Orthostatic Blood Pressure Dysregulation and Polymorphisms of β‐Adrenergic Receptor Genes in Hypertensive Patients. Issue 3 (19th February 2014) - Gao, Ying; Lin, Yahui; Sun, Kai; Wang, Yibo; Chen, Jingzhou; Wang, Hu; Zhou, Xianliang; Fan, Xiaohan; Hui, Rutai
<x xml:space="preserve">Abstract</x> The genetic susceptibility to orthostatic blood pressure dysregulation remains poorly understood. The association between polymorphisms of beta‐adrenergic receptor (β‐AR) genes and orthostatic blood pressure dysregulation in hypertensive patients was investigated. Two polymorphisms of β1‐AR (Arg389/Gly) and β2‐AR (Arg16/Gly) were genotyped in untreated hypertensive patients and normotensive patients. In patients with untreated hypertension, the frequency of β1‐AR Gly389 homozygote was significantly higher in patients with orthostatic hypotension (OH) (P<.0001) and lower in patients with orthostatic hypertension (OHT) (P=.002) as compared with patients with orthostatic normotension (ONT) even after Bonferroni correction. After analysis by sex and adjustment for conventional risk factors, the β1‐AR Gly389 homozygote conferred about a 3‐fold risk of OH and independently predicted a 6.5 mm Hg greater orthostatic SBP decrease (GG −8.9±13 mm Hg vs CC+CG −2.4±12 mm Hg, P<.001) only in female hypertensive patients. The association of β2‐AR Arg16/Gly with OH was not significant after adjustment for conventional risk factors. In normotensive patients, no association was identified between these two polymorphisms and OHT or OH. These results indicated that the β1‐AR Arg389/Gly polymorphism may be associated with increased risk of OH in female hypertensive patients.